Screening rice genotypes for nitrogen efficiency under graded nitrogen application - Bathula, S; Neeraja, C N; Sundaram, R M; Surekha, K; Raghuveer, R P; Subrahmanyam, D; Sanjeeva, R D; Suman, K; Jaldhani, V (Plant Science Today, 2025)
The global application of nitrogen (N) fertilizers continues to rise in efforts to bolster agricultural productivity. However, this surge in usage has led to significant N losses, resulting in low nitrogen use efficiency (NUE) among genotypes and consequent water and air pollution. Although many studies advocate reducing N fertilizer usage, research on screening rice genotypes under graded N application is limited. This study aimed to screen rice genotypes to identify N use efficient cultivars under varying nitrogen levels: N0, N50, N100 and N150. The study also sought to identify key physiological traits linked to grain yield under reduced N conditions. Grain yield decreased by 45.2 % at N0 and 21.4 % at N50 while increasing by 22.3 % at N150 compared to N100. Under reduced N application (N0 and N50), MTU-1010, Vasumati, DRR Dhan-58, Varadhan, Brown Gora SB 92, Tulasi, BV-1692 and DRRH2 exhibited least reduction in grain yield, over N100. Notably, parameters such as ?PSII (actual quantum yield of PSII), ETR (electron transport rate) and qP (coefficient of photochemical quenching) displayed a robust positive association with grain yield under reduced N application compared to the recommended (N100) and high (N150) N application. This underscores the significance of PSII photochemistry in enhancing grain production under limited N. Consequently, leaf chlorophyll fluorescence traits emerge as promising indicators for screening rice genotypes with enhanced NUE under limited N scenarios. In summary, the study conclusively identifies Varadhan as a genotype demonstrating high efficiency in nitrogen utilization, both in terms of grain yield and GYEI, particularly under reduced N regimes.